Knowledge, Skills, and Practices of Global Service Standards Among Graduate Students at Saint Joseph Institute of Technology (SJIT) - Rodelio B. Pasion (RIRAI Publisher, 2024)
This study employed a descriptive research design to examine the knowledge, skills, and practices (KSP) related to global service standards among graduate students at Saint Joseph Institute of Technology (SJIT). Using convenient sampling within the